Foundational Principles for an Organically Constituted World - Bracken, Joseph A. (Theology and science, 2023)
Alfred North Whitehead years ago proposed an organismic approach to physical reality in which the constituent parts of physical entities co-constitute the governing structure of the entity even as the structure constrains the ongoing activity of the constituent parts. In this article, the author proposes that such an organismic approach to reality would be strengthened if one employs a systems-oriented methodology to a Trinitarian understanding of the God-world relationship. The structure of the divine life-system would influence the independent mode of operation of the cosmic process and the mode of operation of the cosmic process would affect the divine persons.